1995
DOI: 10.1128/aac.39.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Study of treatment of congenital Toxoplasma gondii infection in rhesus monkeys with pyrimethamine and sulfadiazine

Abstract: The efficacy of the combination of pyrimethamine and sulfadiazine for the treatment of congenital Toxoplasma gondii infection in rhesus monkeys was studied. The dosage regimen for pyrimethamine and sulfadiazine was established by pharmacokinetic studies in two monkeys. Those studies showed that the distributions of both drugs followed a one-compartment model. The serum elimination half-lives were found to be 5.2 h for sulfadiazine and 44.4 h for pyrimethamine. Sulfadiazine reached a maximum concentration in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Concentrations of pyrimethamine in the fetus ranged from 50% to 100% (mean 66%) of simultaneous serum concentrations in the mothers. These results agree with those obtained in monkeys by Schoondermark-van de Ven and coworkers [782]. Trenque and colleagues concluded that the effective concentrations of both drugs at 14 days after the last dose justifies twice-monthly dosing of the drug combination in cases of documented fetal infection [781].…”
Section: Pyrimethamine Plus Sulfonamidessupporting
confidence: 91%
“…Concentrations of pyrimethamine in the fetus ranged from 50% to 100% (mean 66%) of simultaneous serum concentrations in the mothers. These results agree with those obtained in monkeys by Schoondermark-van de Ven and coworkers [782]. Trenque and colleagues concluded that the effective concentrations of both drugs at 14 days after the last dose justifies twice-monthly dosing of the drug combination in cases of documented fetal infection [781].…”
Section: Pyrimethamine Plus Sulfonamidessupporting
confidence: 91%
“…Our study lacked power to detect an effect of treatment vs no treatment due to small numbers of untreated women. In contrast, a study using a monkey model and a non‐encysting strain of Toxoplasma gondii found that treatment with pyrimethamine–sulphonamide reduced the sensitivity of PCR analysis of amniotic fluid 33 . Failure to detect an effect of treatment may be due to rapid encystment of the parasite, the small number of false negative results or the relatively crude classification of results as positive or negative.…”
Section: Discussionmentioning
confidence: 97%
“…The evidence demonstrating that active infection can be treated and outcome improved developed as follows: antimicrobial treatment of T. gondii in tissue culture animal models eliminates actively replicating parasites and leads to prevention or resolution of signs of disease in these models (Eyles & Coleman 1953a, b, 1955a, Frenkel & Hitchings 1957, Garin et al 1968, 1985, Brus et al 1971, Beverley et al 1973, Feldman 1973, Sheffield & Melton 1975, Grossman & Remington 1979, Garin Paillard 1984, Mack & McLeod 1984, Picketty et al1990 McLeod et al 1992, Hohlfels et al 1994, Schoondermark-van de Ven et al 1995, Derouin 2001, Meneceur et al 2008, Mui et al 2008); treatment of ocular toxoplasmosis, toxoplasmosis in immune-compromised persons of congenital toxoplasmosis in humans abrogates symptoms and signs of active infection and improves outcomes (Perkins et al 1956, Kräubig 1963, Thalhammer 1969, Couvreur et al 1984a, 1993, Desmonts & Couvreur 1984, Daffos et al 1988, Hohlfeld et al 1989, 1994a, b, Dannemann et al 1992, McLeod et al 1992, 2006a, McAuley et al 1994, Patel et al 1996, Torre et al 1998, Boyer 2000, 2005, 2008, Thulliez 2001, Brézin et al 2003, Kim 2006, Berrebi et al 2007, Petrof & McLeod 2002, SYROCOT et al 2007, Kieffer et al 2008), the more rapidly human congenital toxoplasmosis is diagnosed and treated, the shorter the time available for tissue destruction by the parasite and thus the better the outcomes (Remington et al 2006, SYROCOT et al 2007, Kieffer et al 2008); and detection of the infection acquired during the gestation the fetus and rapid initiation of treatment, is often associated with favorable outcomes (Daffos et al 1988, Hohlfeld et al 1989, Foulon et al 1999, Binquet et al 2003, Brèzin et al 2003, Kodjikian et al 2006, Remington et al 2006, Kieffer et al 2008). …”
mentioning
confidence: 99%